Exploring areas of consensus and conflict around values underpinning public involvement in health and social care research: a modified Delphi study. Issue 1 (10th January 2014) - Snape, D; Kirkham, J; Preston, J; Popay, J; Britten, N; Collins, M; Froggatt, K; Gibson, A; Lobban, F; Wyatt, K; Jacoby, A
Abstract : Objective: There is growing interest in the potential benefits of public involvement (PI) in health and social care research. However, there has been little examination of values underpinning PI or how these values might differ for different groups with an interest in PI in the research process. We aimed to explore areas of consensus and conflict around normative, substantive and process-related values underpinning PI. Design: Mixed method, three-phase, modified Delphi study, conducted as part of a larger multiphase project. Setting: The UK health and social care research community. Participants: Stakeholders in PI in research, defined as: clinical and non-clinical academics, members of the public, research managers, commissioners and funders; identified via research networks, online searches and a literature review. Results: We identified high levels of consensus for many normative, substantive and process-related issues. However, there were also areas of conflict in relation to issues of bias and representativeness, and around whether the purpose of PI in health and social care research is to bring about service change or generate new knowledge. There were large differences by group in the percentages endorsing the ethical justification for PI and the argument that PI equalises power imbalances. With regard to practical implementation of PI, research support infrastructures were reported as lacking. Participants reported shortcomings in the uptake and practice of PI. Embedding PI practice and evaluation in research study designs was seen as fundamental to strengthening the evidence base. Conclusions: Our findings highlight the extent to which PI is already embedded in research. However, they also highlight a need for 'best practice' standards to assist research teams to understand, implement and evaluate PI. These findings have been used in developing a Public Involvement Impact Assessment Framework (PiiAF), which offers guidance to researchers and members of the public involved in the PI process.